2019
DOI: 10.1186/s40104-018-0308-3
|View full text |Cite
|
Sign up to set email alerts
|

Piglet gut microbial shifts early in life: causes and effects

Abstract: The gut microbiome has long been known to play fundamentally important roles in the animal health and the well-being of its host. As such, the establishment and maintenance of a beneficial gut microbiota early in life is crucial in pigs, since early gut colonizers are pivotal in the establishment of permanent microbial community structures affecting the health and growth performance of pigs later in life. Emphasizing this importance of early gut colonizers, it is critical to understand the factors impacting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
298
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(325 citation statements)
references
References 67 publications
(93 reference statements)
22
298
4
1
Order By: Relevance
“…Results from Man-Whitney tests showed that alpha diversity at all stages were different ( P < 0.001) to each other. This was in accordance with similar studies in pigs and other organisms (Frese et al, 2015; Guevarra et al, 2019); Lu et al, 2018). The increase in alpha diversity with age was similar to what previously found by different authors (Chen et al, 2017; Kim et al, 2011; Looft and Allen, 2012; Thompson et al, 2008).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Results from Man-Whitney tests showed that alpha diversity at all stages were different ( P < 0.001) to each other. This was in accordance with similar studies in pigs and other organisms (Frese et al, 2015; Guevarra et al, 2019); Lu et al, 2018). The increase in alpha diversity with age was similar to what previously found by different authors (Chen et al, 2017; Kim et al, 2011; Looft and Allen, 2012; Thompson et al, 2008).…”
Section: Resultssupporting
confidence: 94%
“…Our results suggested that diversity at weaning might not be an accurate predictor of growth, carcass and meat quality traits which agreed with Huttenhower et al (2012). Alpha diversity was reported to be associated with gut health of animal and associated with the normal physiology of host animals (Guevarra et al, 2019)). The major role could include the normal function of gut, enhance immune response and play active role in digestion and utilization of nutrients.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Despite the further increase in species richness (Chao1) and diversity (Shannon), differences in the microbiota composition were not as pronounced between days 28 (preweaning) and 97 (postweaning) as it might have been expected from previous work [35], which can be linked to the early introduction of solid feed in the present study. Commonly, weaning implies an abrupt shift from a high-fat, low-carbohydrate milk as the main feed source towards a high-carbohydrate, low-fat cereal-based diet, leading to taxonomic [36] and functional [28] shifts in the gut microbiota which are necessary for adaption to the new feed source. Interestingly, amylolytic Ruminococcaceae did not further increase as could be expected for starch-and hemicellulose-degrading bacteria but decreased from day 28 to 97 of life.…”
Section: Discussionmentioning
confidence: 99%
“…from proximal to distal end of the intestinal tract and as pigs age (1,64,65), resulting in exposure to a larger and more diverse microbially-derived antigenic repertoire in distal intestinal regions and in older pigs. Correspondingly, percentages of CD27 + IETs were reduced at the distal but not proximal end of the intestinal tract as pigs aged, indicating distally-located intestinal IETs may be activated at higher frequencies, and the frequency of activation accrues with age (and presumably, antigen exposure).…”
mentioning
confidence: 99%